Sharia Business Contracts - Ibnudin; Indra Sudrajat (Values: Jurnal Kajian Islam Multidisiplin, 2025)
The term engagement used in the Civil Code is known in Islam as aqad (contract in Indonesian). Jumhur Ulama defines a contract as "a relationship between an agreement and a promise that is justified by the syara' which gives rise to legal consequences for its object." A pledge is one of the most important elements in forming a contract. This agreement is in the form of an agreement and a statement. Ijab is a statement from someone (the first party) to offer something. Kabul is a statement from someone (the second party) to accept or grant an offer from the first party. If the consent and Kabul made by both parties are related and in accordance, then it happens between them. Sharia Bank is a financial institution based on Islamic Sharia. On the macro side, Sharia Bank positions itself as an active player in supporting and playing investment activities in the community. On the one hand, Sharia Bank encourages and invites the community to actively participate in investing through sharing their products, while on the other hand Sharia banks are active in investing in the community. Apart from that, at a micro level, Sharia banks are financial institutions that guarantee that all their operational activities, including the financial products and services they offer, are in accordance with Islamic principles.